The Effect Of Self Efficacy Towards Independency Level Of Post-Stroke Patient In General Hospital Neuro Policlinic Ulin Banjarmasin - Gaghauna, Eirene E.M; Santoso, Bagus Rahmat (Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Background: Stroke is a disease of brain function disorder of the nerves in the form of local and global roomates have impact to physical and physcological. Stroke is the third causes of death in Indonesia and in South Kalimantan every 9.2 per mill areas, stroke cases had happened. There are 1258 cases in 2015 hospitalized in Ulin General Hospital.Purpose: To analyze the effect of self-efficacy on towards the Independence level of post-stroke patient in general hospital neuro policlinic Ulin BanjarmasinMethods: The methodology that use in this study is descriptive analytics, the total respondents in this study is 33 respondents. Collecting the data in this study is using the Stroke Self-Efficacy and Barthel index questionare. The Data Analyzed by Kendal Tau test.Result: According to this study to 33 respondent Obtained results. The respondents who have high self efficafy as 25 (75.7%), moderate self efficacy as many as seven respondents (21.2%) and has low self-efficacy is one respondents (3.0%) and to the independence level of post-stroke patient variables who had Categorized to independence are 14 respondents (42.4%), need minimal assistance 5 respondents (15.2%), partially need assistance in three respondents (9.0%), dependece assistance is five respondents (15.2%) and total assistance in six respondents (18.2%). the analysis result by Kendal Tau get p value = 0.044. the strength of the correlation is r = 310 it was statethat signifficant there is a moderate correlation and the direction are positive correlation.Conclusion: There signifficant There is correlation between self-efficacy to the Independence level of post-stroke patient